STUDI KETERSEDIAAN UNSUR HARA MAKRO PADA PROSES PENGOLAHAN LIMBAH CAIR INDUSTRI PERKEBUNAN KELAPA SAWIT PT FARINDA BERSAUDARA - Riski Amalia Rusdi; Sukariyan; Abdul Rasyid Zarta (Politeknik Pertanian Negeri Samarinda, 2022)
This research is motivated by the importance of managing liquid waste in the oil palm plantationindustry of PT. Farinda Bersaudara, whose aim is to determine the potential availability ofmacronutrient content in their liquid waste, with the method used, namely by taking liquid waste in thesewage treatment pond (1,5 and 8) with each pond taken a sample that is put in a bottle. 1.5 literpackages in each pond, samples were packed and sent to the laboratory for analysis of macronutrientcontent (N, P, K, Ca, Mg, Na and pH).The results showed that the content of macronutrients in theliquid waste pond no 5 from the palm oil plantation waste treatment plant showed that the organicchemical content was better than pond 1 and pond 8